PENYELESAIAN SENGKETA WARIS PADA MASYARAKAT ADAT MINANGKABAU YANG DILAKUKAN OLEH NINIK MAMAK: Resolution Of Heritage Disputes In The Minangkabau Traditional Community Carried Out By Ninik Mamak - Trishya Pradicintia; Ning Adiasih (Reformasi Hukum Trisakti, 2025)
Mediation is one of the alternative dispute resolution methods considered effective in reducing prolonged disputes. Mediation alternative is not only conducted in public manner, but also be carried out through traditional customs. One of the customes that establish mediation is the Minangkabau custom. In Minangkabau traditional society, mediation is applied to settle disputes among clans or family groups. There is problem issues namely the role of ninik mamak as a mediator and how ninik mamak conducts mediation. This research is located at Kanagarian Guguak Kuranji Hilir, Sub district Sungai Limau, District Padang Pariaman, province West Sumatra. This study uses a socio - legal approach, integrating insights from both social sciences and law. This research applies mixed- methods approach, combining primary data from interviews with ninik mamak and their relatives, and secondary data from literature reviews to suplement the research. The result and the conclusion indicate that the role of ninik mamak remains relevant nowadays, and ninik mamak as a mediator is consistent with government regulation No. 54 of year 2000. The implementation of mediation which is applied by Ninik Mamak in line with the regulation of Supreme Court No.1 year of 2016.